Impact of Osteoarthritis on Household Catastrophic Health Expenditures in Korea - Kim, Hyoungyoung (J Korean Med Sci, 2018)
BACKGROUND: Osteoarthritis (OA) is a disease of old age whose prevalence is increasing. This study explored the impact of OA on household catastrophic health expenditure (CHE) in Korea. METHODS: We used data on 5,200 households from the Korea Health Panel Survey in 2013 and estimated annual living expenses and out-of-pocket (OOP) payments. Household CHE was defined when a household's total OOP health payments exceeded 10%, 20%, 30%, or 40% of the household's capacity to pay. To compare the OOP payments of households with OA individuals and those without OA, OA households were matched 1:1 with households containing a member with other chronic disease such as neoplasm, hypertension, heart disease, cerebrovascular disease, diabetes, or osteoporosis. The impact of OA on CHE was determined by multivariable logistic analysis. RESULTS: A total of 1,289 households were included, and households with and without OA patients paid mean annual OOP payments of $2,789 and $2,607, respectively. The prevalence of household CHE at thresholds of 10%, 20%, 30%, and 40% were higher in households with OA patients than in those without OA patients (P < 0.001). The presence of OA patients in each household contributed significantly to CHE at thresholds of 10% (odds ratio [OR], 1.48; 95% confidence interval [CI], 1.16–1.87), 20% (OR, 1.29; 95% CI, 1.01–1.66), and 30% (OR, 1.37; 95% CI, 1.05–1.78), but not of 40% (OR, 1.17; 95% CI, 0.87–1.57). CONCLUSION: The presence of OA patients in Korean households is significantly related to CHE. Policy makers should try to reduce OOP payments in households with OA patients.